“Me Too”: Epistemic Injustice and the Struggle for Recognition - Jackson, Debra L. (Feminist Philosophy Quarterly, 2018)
Congdon (2017), Giladi (2018), and McConkey (2004) challenge feminist epistemologists and recognition theorists to come together to analyze epistemic injustice. I take up this challenge by highlighting the failure of recognition in cases of testimonial and hermeneutical injustice experienced by victims of sexual harassment and sexual assault. I offer the #MeToo movement as a case study to demonstrate how the process of mutual recognition makes visible and helps overcome the epistemic injustice suffered by victims of sexual harassment and sexual assault. I argue that in declaring “me too,” the epistemic subject emerges in the context of a polyphonic symphony of victims claiming their status as agents who are able to make sense of their own social experiences and able to convey their knowledge to others.
Keywords: #metoo; 2000 à aujourd'hui; 2010-2019; approches et analyses; corps; cours; cycles supérieurs; discipline; fem9000; harcèlement sexuel; injustices herméneutiques; injustices testimoniales; injustices épistémiques; philosophie; philosophie féministe; périodes historiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; violences sexistes et sexuelles; éthique